Fostering Accessibility in Geoscience Training Programs. (29th October 2013) - Atchison, Christopher L.; Libarkin, Julie C.
<x xml:space="preserve">Abstract</x> New insight has emerged over the past decade into mechanisms for improving diversity across the geosciences. Publications and programs associated with the American Geosciences Institute, the U.S. National Science Foundation, and the International Association for Geoscience Diversity (IAGD), as well as technical sessions and diversity receptions at geoscience society meetings, are promoting geoscience diversity. While these efforts to diversify the geoscience workforce have improved awareness and generated programs aimed at increasing graduation rates across genders [Holmes et al., 2008] and ethnicities [O'Connell and Holmes, 2011], people with physical disabilities continue to be underrepresented in the geoscience workforce [Locke, 2005; Atchison and Martinez‐Frias, 2012].